Evolution of Lower Brachyceran Flies (Diptera) and Their Adaptive Radiation with Angiosperms - Zhang, Qingqing; Wang, Bo (Frontiers in Plant Science, 2017)
The Diptera (true flies) is one of the most species-abundant orders of Insecta, and it is also among the most important flower-visiting insects. Dipteran fossils are abundant in the Mesozoic, especially in the Late Jurassic and Early Cretaceous. Here, we review the fossil record and early evolution of some Mesozoic lower brachyceran flies together with new records in Burmese amber, including Tabanidae, Nemestrinidae, Bombyliidae, Eremochaetidae, and Zhangsolvidae. The fossil records reveal that some flower-visiting groups had diversified during the mid-Cretaceous, consistent with the rise of angiosperms to widespread floristic dominance. These brachyceran groups played an important role in the origin of co-evolutionary relationships with basal angiosperms. Moreover, the rise of angiosperms not only improved the diversity of flower-visiting flies, but also advanced the turnover and evolution of other specialized flies.